Technology Acceptance Model as a Mediator Explaining Factors Affecting Online Education - Elsayed, Mayar Farrag Singab; Shabbat, Manal Elsayed Abdelhamid (The Arab Journal of Administration, 2025)
Purpose – This study aims to provide educators with information concerning factors impacting the student’s willingness to use online learning. This is explained by the mediator technology acceptance model (TAM). The study investigates the external factors and the mediating effect of the perceived ease of use, and perceived usefulness on the intention to use online learning. Design/methodology/approach Results are obtained from surveying 202 university students, 80 of which are undergraduates, while 122 are postgraduates. Public and private universities are represented in the sample, as 53% of the sample are private university students, while 47% are public students. 62.4% are students outside Cairo, whereas 37.6% are from residential areas outside Cairo. Smart PLS 3 has been used to test the hypothesis, directly and indirectly involving testing mediation. Findings - There is no direct relation between the instructor’s online self-efficacy, student online self-efficacy, and the student willingness to use online education. Nevertheless, there is a significant direct relationship between organizational support and student intention to use online education. Originality/value – This research adds to the knowledge accumulation of online learning studies, it discusses online learning in the context of Egypt’s higher education during COVID 19 crises. As, the Egyptian case provides an enriched applied case of a developing country that could face the negative repurctions of COVID 19 on the students in the higher education system. Data represent the educational form and level that might affect student behavioral intention to learn online. Having the TAM as the mediator affects the relations between variables. This study will provide educators responsible for the management and development of online learning with significant information about how students perceive online learning and ways to encourage adoption by students.